Logistic characterization of the dairy supply chain - Salamanca Gómez , Tatiana Paola; García-Cáceres, Rafael Guillermo; Espitia-Cubillos, Anny Astrid (Cuadernos de Administración, 2023)
The Colombian dairy supply chain is described and characterized in terms of its agents, interactions, stages and links, among other aspects that are relevant to the production and marketing of milk and dairy products. The characterization methodology comprises four steps: evaluation of the global and national production of the dairy supply chain, identification and description of its links and stages, assessment of the value added by its agents and links, and detailed analysis of its performance specificities. In addition, relevant weaknesses were observed in the upstream stage, which not only has the least economic leverage but is also the most vulnerable stage since it absorbs most of the risk in the chain. The current study revealed weakness in the upstream phase, which is the most vulnerable part of the chain, since it absorbs most of the risk and has the lowest financial leverage. As a consequence, it usually faces profitability problems. This is actually a common trend in the literature on the topic, as seen in previous agribusiness SC analyses, wherein similar weaknesses have been revealed.